The effect of an education programme (MEDIAS 2 BSC) of non‐intensive insulin treatment regimens for people with Type 2 diabetes: a randomized, multi‐centre trial. Issue 8 (2nd April 2017) - Hermanns, N.; Ehrmann, D.; Schall, S.; Maier, B.; Haak, T.; Kulzer, B.
Abstract: Aims: A self‐management oriented education programme (MEDIAS 2 BSC) for people with Type 2 diabetes who are on a non‐intensive insulin treatment regimen was developed. In a randomized, multi‐centre trial, the effect of MEDIAS 2 BSC was compared with an established education programme that acted as a control group. Methods: The primary outcome was the impact of MEDIAS 2 BSC on glycaemic control. Secondary outcomes included the incidence of severe hypoglycaemia, hypoglycaemia unawareness, diabetes‐related distress, diabetes knowledge, quality of life and self‐care behaviour. Results: In total, 182 participants were randomized to the control group or MEDIAS 2 BSC [median age 64.0 (interquartile range 58.0–68.5) vs. 63.5 (57.0–70.0) years; HbA1c 62.8 ± 12.7 mmol/mol vs. 63.7 ± 14.0 mmol/mol; 7.9% ± 1.2% vs. 8.0% ± 1.3%]. After a 6‐month follow‐up, there was a mean decrease in HbA1c of 3.5 mmol/mol (0.32%) in the control group and 6.7 mmol/mol (0.61%) in MEDIAS 2 BSC. After adjusting for baseline differences and study centre, the mean difference between the groups was −3.3 mmol/mol [95% confidence interval (CI) −0.54 to −5.90 mmol/mol] [−0.30% (95% CI −0.05 to −0.54)] in favour of MEDIAS 2 BSC ( P = 0.018). There were no increases in severe hypoglycaemia or hypoglycaemia unawareness. The education programmes had no significant effects on psychosocial outcome variables. Conclusion: MEDIAS 2 BSC was more effective in lowering HbA1c than the control condition. MEDIAS 2 BSC is a safe educational tool that improves glycaemic control without increasing the risk for hypoglycaemia. (Clinical Trials Registry No; NCT 02748239) What's new?: Most people who have Type 2 diabetes and are treated with insulin are on a non‐intensified insulin regimen. A modern, self‐management education programme was developed and evaluated for this specific group of people. This newly developed education programme supports people who have Type 2 diabetes in achieving their glycaemic targets by titrating their insulin doses. Evaluation of the results indicates that the newly developed education programme can enhance the efficacy of insulin treatment for glycaemic control.